Plato on the Love of Individuals - MOONEY, T. Brian (Institutional Knowledge at Singapore Management University, 2002)
A perennial problem in the philosophy of love has centred around what it is to love persons qua persons. Plato has usually been interpreted as believing that when we love we are attaching ourselves to qualities that inhere in the objects of our love and that these qualities transcend the objects. Vlastos has argued, along with Nussbaum, Price and many others that such an account tells against a true love of persons as unique and irreplaceable individuals. I argue that Plato’s account of love as presented in the Lysis and Symposium is not so easily rejected. My concern is both to show that Plato can meet the objections and that his theory can still offer helpful insights into the understanding of love in our own lives. In particular I will identify two manners of loving persons; one which is context and individual specific, and another which might be termed metaphysical, thereby preserving aspects of the Platonic ascent of love. I will further argue that the two aspects are often non–controversially linked, and that such linking helps explain something of the mysterious nature of love.